Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kepuasan Kerja pada Pegawai Perumda Manuntung Sukses Kota Balikpapan - Rahya Nasywa Balqis; Tutik Yuliani; Imam Arrywibowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of motivation, work discipline, and work environment on job satisfaction among employees of Perumda Manuntung Sukses Balikpapan. The research employed a quantitative approach with a saturated sampling technique involving 45 employees. Data were collected through observation, interviews, and Likert-scale questionnaires and analyzed using Partial Least Square (PLS) with SmartPLS software. The findings reveal that motivation has a positive and significant effect on job satisfaction, followed by work discipline and work environment, which also show positive and significant influences. The R-Square value of 0.839 indicates that 83.9% of job satisfaction is explained by the three variables, with motivation as the most dominant factor.